Hardware, Software, and Human in the Loop Education Supported with Social Network Analysis and Mining - Karakose, Mehmet (Ieee, 2016)
The usability of comparable technology in the higher education is very important for supporting knowledge management at industry assisted technology. An Information Technology (IT) platform with administrators, instructors, and students is necessary to achieve a powerful learning content. This process requires an educational lifeloop management approach. This approach provides some features such as active and responsible students according to passive students, differentiated instructional methods according to standard instructional methods, student-focused learning experiences according to lecturer-based instructional methods, and analyzed, sorted, and provided student data in real time. This paper proposes a new conceptual model for improvement of education lifeloop management approach. The proposed model consists of three main stages and two supporting stages. This model has a natural loop between three main stages supported with two stage. The proposed overall approach has a loop that renew with a continuously loops and a structure that includes effects of all factors.
15th International Conference on Information Technology Based Higher Education and Training (ITHET) -- SEP 08-10, 2016 -- Istanbul, TURKEY
Keywords: Education Lifeloop Management; Hardware in the Loop Education; Higher Education; Human in the Loop Education; Social Network Analysis; Software in Loop Education